Tuning the Electronic and Chemical Properties of Graphene Quantum Dots via CO2 Adsorption: Insights from DFT Calculations - Hussein, Diyaa; Nimar, Fouad; Ben Ahmed, Ali (University of Thi-Qar Journal of Science, 2025)
The effects of edge modification with carbon dioxide (CO2) on the electronic and structural properties of graphene quantum dots (GQDs) are analyzed in this work with density functional theory. Pristine GQDs and GQDs with one to four AC molecules edge modification are examined for their energetic and chemical properties. The study reveals a substantial reduction in the energy gap through CO2 edge modification, with a minimum of 91.2% energy gap reduction for GQDs modified with four CO2 molecules. Changes to the bandgap modulated the Fermi level, highest occupied molecular orbital and the lowest unoccupied molecular orbital energies, showing the electronic properties of GQDs could be tuned by edge engineering. Furthermore, global chemical descriptors (ionization potential, electronic affinity, chemical hardness, and electrophilicity) at the edge modification were all notably affected. Edge modification with CO2 was found to increase electrophilicity and lower chemical hardness, resulting in GQDs exhibiting higher inherent activity and greater electron-accepting ability. The results presented in this study demonstrate that edge modification again CO2 provides a powerful vehicle for tuning the electronic and chemical behavior of GQDs and suggest the use of GQDs as an advanced candidate for electronics and sensing at the nanoscale.